Characterization of Meloidogyne spp. and population density of phytoparasitic nematodes associated with alliaceae crops in the Arequipa region, Peru - Peralta Ccayahuallpa, Victor Alexi (2024)
Alliaceae crops includes several species of agricultural importance for the Arequipa region, among them the onion is the most produced in the country, however, these crops are affected by phytoparasitic nematodes, including Meloidogyne spp. which causes significant losses in the yield. The aim of the present study was to characterise the root-knot nematode (Meloidogyne spp) and determine the population density of phytoparasitic nematodes in alliaceae crops in the main producing localities of the Arequipa region. Samples of roots and soil were collected in onion, chinese onion, leek and chives crops in the provinces of Arequipa, Castilla, Caylloma and Islay. The identification of nematode genus was found by morphological characteristics and the characterization of Meloidogyne were performed by perineal patterns and electrophoretic pattern of esterase (Est). In the 38 soil samples, different genus of plant-parasitic nematodes was found: Aphelenchus, Dorylaimus, Helicotylenchus, Hemicycliophora, Meloidogyne, Mesocriconema, Mononchus, OGMA, Pratylenchus, Rotylenchus, Tylenchus, Xiphinema and free-living nematodes, in root samples, eight populations of Meloidogyne spp. were found. distributed among three species: (1) M. incognita phenotype Est I1, Rm: 1.0 with 33.33% of frequency and Est I2, Rm: 1.03, 1.07 (50%); (2) M. javanica Est J3, Rm: 1.03, 1.24, 1.37 (16.67%) and an atypical species named Meloidogyne sp. Rm: 0.85 (33.33%). The identification of genus and species phytoparasitic nematodes in alliaceae will allow the adoption of more efficient integrated management measures, because have a distinct parasitism behavior.